CLINICAL ASSOCIATIONS AND PROGNOSTIC IMPLICATIONS OF REPAIR TISSUE PROLIFERATION IN EYES WITH RETINAL PIGMENT EPITHELIUM TEARS. Issue 3 (March 2022) - Cicinelli, Maria V.; Rabiolo, Alessandro; Montesano, Giovanni; Marchese, Alessandro; Barresi, Costanza; Introini, Ugo; Parodi, Maurizio B.; Bandello, Francesco
Abstract : Purpose: To investigate demographic and clinical factors influencing the longitudinal changes of retinal pigment epithelium (RPE) dehiscence area after RPE tears, including the presence of RPE tear-associated repair proliferation (TARP), and identify factors associated with TARP development over follow-up. Methods: Retrospective, single-center, observational cohort study of patients with a history of macular neovascularization and RPE tear. The area of RPE dehiscence was measured on repeated short-wavelength fundus autofluorescence imaging. Associations between covariates and RPE dehiscence areas were tested with multivariable linear mixed models. Associations between TARP development and clinical variables were investigated with Cox regression models. Factors associated with visual acuity changing rates were explored with linear mixed models. Results: Thirty-seven eyes of 36 patients were included in this study and followed for a median time of 18 months. Tear-associated repair proliferation was identified in 27 eyes (73%). The median time for TARP detection was 112 days; none of the investigated factors was significantly associated with TARP occurrence. The presence of TARP (estimate: −0.042 mm 2 /month; P = 0.001) and female gender (estimate: −0.035 mm 2 /month; P = 0.006) were associated with slower rates of RPE dehiscence enlargement over time. Faster rates of visual improvement were observed in eyes with TARP compared with those without TARP (estimate = −0.010 logarithm of the minimum angle of resolution/month if TARP was present; P = 0.008). Conclusion: Retinal pigment epithelium tear repair with TARP and female gender were associated with slower RPE degeneration after RPE tears. The presence of TARP was associated better visual prognosis. Additional research on factors promoting TARP development may have therapeutic and prognostic implications. Abstract : Supplemental Digital Content is Available in the Text. Retinal pigment epithelium tears secondary to macular neovascular membrane may enlarge over time. Enlarging retinal pigment epithelium dehiscence is characterized by sharply demarcated borders and absence of perilesional hyperautofluorescence. The presence of retinal pigment epithelium tear–associated repair proliferation is associated with slower rates of retinal pigment epithelium dehiscence expansion.